A Straightforward Electrochemical Approach to Imine‐ and Amine‐bisphenolate Metal Complexes with Facile Control Over Metal Oxidation State. Issue 4 (15th April 2016) - Chapman, Michael R.; Henkelis, Susan E.; Kapur, Nikil; Nguyen, Bao N.; Willans, Charlotte E.
Abstract: Synthetic methods to prepare organometallic and coordination compounds such as Schiff‐base complexes are diverse, with the route chosen being dependent upon many factors such as metal–ligand combination and metal oxidation state. In this work we have shown that electrochemical methodology can be employed to synthesize a variety of metal–salen/salan complexes which comprise diverse metal–ligand combinations and oxidation states. Broad application has been demonstrated through the preparation of 34 complexes under mild and ambient conditions. Unprecedented control over metal oxidation state (M II/III/IV where M=Fe, Mn) is presented by simple modification of reaction conditions. Along this route, a general protocol‐switch is described which allows access to analytically pure Fe II/III –salen complexes. Tuning electrochemical potential, selective metalation of a Mn/Ni alloy is also presented which exclusively delivers Mn II/IV –salen complexes in high yield. Abstract : Smooth salen ! Electrochemical synthesis has provided easy access to 34 complexes of diverse metal–ligand combinations. Facile control over metal oxidation state was possible through slight modification of reaction conditions. Remarkably, selective metallation using a Mn/Ni alloy furnished analytically pure Mn complexes in high yield.